Pentecostal Moral Bricolageand Women's Survival in Zimbabwe's Kukiya-Kiya Economy: Lessons from Beitbridge Border Post - Bvute, Tsitsidzashe (Journal for the study of religion, 2025)
This study examines the ethical considerations of Zimbabwean Pentecostal women in cross-border trade. I examine how they navigate the ethical tensions between religious convictions, which value hard work and moral discipline, and the survival imperatives of an informal economy marked by systemic corruption and punitive policies that penalize the poor. Using a hybrid ethnographic methodology, this study combines in-person and online interviews and participatory observations to gather data from 22 traders. The key finding is that these women do not abandon their faith-based ethics; instead, they engage in moral bricolage. They reinterpret morally ambiguous practices such as bribery and smuggling, through a Pentecostal lens, framing these as divine tests and forms of sowing seeds for future improvisation (kukiya-kiya) in a corrupt system. The study's primary contribution is a nuanced theorization of how Pentecostalism provides a language of justification, enabling agency, and critiquing the state's failure. It moves beyond the binaries of piety and corruption or formality and informality, offering a critical understanding of religious ethics, gendered power, and economic survival in Zimbabwe's crisis.